2016
DOI: 10.24953/turkjped.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Associations of lean and fat mass measures with whole body bone mineral content and bone mineral density in female adolescent weightlifters and swimmers

Abstract: Body composition and sport participation have been associated with bone mass. The purpose of this study was to determine the associations of lean and fat mass measures with whole body bone mineral content (BMC) and bone mineral density (BMD) in female adolescent weightlifters, swimmers and non-athletic counterparts. This study included a total of 25 female adolescents (mean age: 15.3±1.1 years). Body composition and bone mass were measured by dual-energy X-ray absorptiometry. In most of the studied variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Study in Turkey 2016 found that weight lifters (non-endurance sport) have greater body fat than swimming athletes (endurance sport). 26 Body fat percentage in swimming athletes is higher than other athletes in endurance sports (medium distance running, long-distance running, and rowing). These results were in line with research in Brazil 2017 which showed female swimming athletes has a higher body fat percentage than other athletes such as running, gymnastics, and rowing since these sports require more movement.…”
Section: Resultsmentioning
confidence: 95%
“…Study in Turkey 2016 found that weight lifters (non-endurance sport) have greater body fat than swimming athletes (endurance sport). 26 Body fat percentage in swimming athletes is higher than other athletes in endurance sports (medium distance running, long-distance running, and rowing). These results were in line with research in Brazil 2017 which showed female swimming athletes has a higher body fat percentage than other athletes such as running, gymnastics, and rowing since these sports require more movement.…”
Section: Resultsmentioning
confidence: 95%
“…However, adolescents with AN had lower LBMI Z ‐score than adolescents with AAN, and adolescents without a prior history of overweight had lower LBMI Z ‐score than adolescents with a prior history of overweight. Deficits in lean mass may contribute to low BMD (Koşar, ). Adolescents with AAN and a prior history of overweight did not demonstrate significant deficits in LBMI Z ‐score.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to preceding studies that investigated adolescent female wrestlers [ 9 , 12 ], the present elite wrestlers demonstrated no outstanding features concerning the stature, the body mass, and the BMI ( Table 2 , stature: 151.9 ± 3.8 cm in LW and 161.9 ± 4.6 cm in HW, body mass: 47.2 ± 2.5 kg in LW and 61.6 ± 5.8 kg in HW, BMI: 20.5 ± 1.1 in LW and 23.5 ± 2.3 in HW). When compared with athletes other than wrestlers [ 14 , 26 , 27 , 28 , 29 ], the present wrestlers did not have particularly large BMI ( Table 2 ). Despite the importance of muscle development in wrestling, the present elite female wrestlers showed ordinary BMI, probably because competitive wrestling is conducted in a weight-class system.…”
Section: Discussionmentioning
confidence: 58%